Quel est l'impact d'un moment de formulation d'hypothèses sur l'investigation menée par des élèves français (grade 7, 12 ans) durant un enseignement sur la flottabilité ? - ANTONIN BOYER; DAMIEN GIVRY (Metaichmio Publications, 2017)
Our study shows the impact of one formulation of hypotheses on students' ideas and their manipulations during the handling of an inquiry based teaching on buoyancy. The same teacher taught two lessons (with and without writing previsions) to 12-13 years old students (grade 7). The analysis of videos and written works of 24 students shows that formulation of previsions favors ideas close to the physic point of view and material solutions more in agreement with it. It also, shows that students do not test their hypotheses and speak about different ideas during formulation of hypotheses and inquiry.